Linguistic Predictors of Problematic Drinking in Alcohol-related Facebook Posts - Van Swol, Lyn M. (J Health Commun, 2020)
Emerging adults often increase problematic drinking during college. Although they generally do not seek help for problematic drinking, college students discuss their drinking on social media. This study followed college students’ Facebook profiles from the inception of their attendance at a university and identified alcohol-related posts. Within 28 days of their first alcohol-related Facebook post, participants were interviewed to assess problematic drinking (binge drinking episodes and number of drinks). Linguistic analysis of alcohol-related Facebook posts found that use of negative emotion language and swear words were related to problematic drinking, in support of proposed hypotheses. Results are situated within alcohol use disorder and health research examining the link between problematic drinking and anxiety, deviant behavior, and negative emotions.